The Role of AI-Powered Learning Tools in Enhancing Vocabulary Acquisition for ESP/EFL Students: Teachers’ and Students’ Perceptions at M’Sila University - Heythem Khatim; Manal Ben Salah (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
Abstract This study investigates the perceptions of teachers and students regarding the use of AI-powered learning platforms to enhance vocabulary acquisition in English for Specific Purposes (ESP) courses at M’sila University. Considering the growing of artificial intelligence in education, particularly in language learning, the research explores how these AI-driven platforms are perceived in terms of their effectiveness, usability, and impact on learning outcomes. The study uses a quantitative descriptive research approach, collecting data through questionnaires to examine ESP teachers’ and students’ perspectives, and therefore, descriptive statistics and inductive data are applied to find the sequences and group differences. Findings reveal diverse perspectives: students’ perceptions of AI-powered learning tools showed a mean of 3.84 (on a 5-point scale), while teachers’ perceptions reached a slightly higher mean of 3.94. Usage-related responses were slightly lower, with a mean of 3.41 for students and 3.40 for teaching practices. Although many participants recognize the potential of AI tools to provide personalized, adaptive, and engaging vocabulary practice, in addition to challenges such as technical limitations, lack of domain-specific vocabulary, and user resistance are also highlighted in this research. The research pinpoints important elements which impact the effective integration of AI-powered platforms into ESP teaching, including teacher training, accessibility, and alignment with specialized vocabulary needs.
Keywords: Keywords: ESP teachers’/ students’ perceptions; AI-powered learning platforms; Vocabulary acquisition; Integration of AI in ESP.